Bank Credit Restructuring for Micro, Small and Medium Enterprises Due to the Covid-19 Pandemic - Berlianty, Teng; Akyuwen, Rory Jeff; Tas’an, Darma Perdana (Faculty of Law, Universitas Pattimura, 2023)
The presence of the corona virus or coronavirus disease 2019 (Covid-19) has an impact on all aspects of human life, including in the fields of financial institutions and banking. The aim of this research is to examine the legal protection for debtors of Micro, Small and Medium Enterprises due to the Covid-19 pandemic in Ambon City, as well as the criteria for debtors of Micro, Small and Medium Enterprises who meet the credit restructuring requirements due to the Covid-19 pandemic. The method used in this study is a normative juridical method with a statutory approach and a conceptual approach. The legal materials studied consisted of primary legal materials, secondary legal materials, and tertiary legal materials through literature studies which were then analyzed qualitatively. Results of the Research, he implementation of credit agreements between banking institutions and debtors of Micro, Small and Medium Enterprises in Ambon City due to the Covid-19 pandemic is affected by the Covid-19 pandemic. Legal protection is carried out based on government policies through credit restructuring efforts for debtors who have difficulty fulfilling their obligations, which are carried out among others by reducing credit interest rates, extending credit terms, reducing loan interest arrears, reducing loan principal arrears, adding credit facilities. The criteria for debtors of Micro, Small and Medium business debtors who meet the requirements for credit restructuring due to the Covid-19 pandemic consist of 2 main criteria, namely the business of the debtor is indeed affected by the Covid-19 pandemic, and also the debtor's good faith in paying off credit installments.